Histopathological patterns of skin adnexal tumours in Ibadan, South-west Nigeria (2022)
Background: Skin adnexal tumours (SATs) are tumours that differentiate towards one or more of the adnexal structures of the skin. The aim of this study was to determine the incidence of SATs in Ibadan and to correlate them with age, sex and anatomic location. Methods: This is a 10-year retrospective study of all SATs in the Department of Pathology, University College Hospital, Ibadan. The clinicopathological data were obtained from the department’s records for the given period. Haematoxylin and eosin stained sections obtained from formalin fixed paraffin embedded tissue blocks were examined to confirm the diagnosis and special stains such as periodic acid Schiff staining done where necessary. Cases of SATs were further classified into benign and malignant tumours. Results: Twenty-seven cases of SATs were reviewed over the study period. Tumours from the sweat glands formed the largest group (55.6%) with trichoepithelioma being the most common subtype, followed by tumours with follicular differentiation (40.7%) and sebaceous tumours (3.7%). There was a slight female predominance with a male-to-female ratio 1:1.07. The highest number of tumours was seen in the fourth decade of life (23%). Benign tumours made up the majority of cases (85.2%). The most common location was the head and neck with 40.8% of cases. Conclusion: SATs are not uncommon among Nigerian patients. These tumours are mostly benign and are present commonly in the head and neck location.